Effect of alternating current frequency on corrosion behavior of X80 pipeline steel in coastal saline soil. (February 2021) - Qin, Qingyu; Wei, Boxin; Bai, Yunlong; Fu, Qi; Xu, Jin; Sun, Cheng; Wang, Chuan; Wang, Zhenyao
Highlights: Effect of AC frequency on corrosion of X80 steel has been investigated. AC accelerates corrosion of X80 steel. Corrosion rate is a power function of AC frequency. At low AC frequencies, corrosion product films contain more defects than those at high frequencies. AC does not change the type of corrosion products. Abstract: Effects of alternating currents (AC) with different frequencies on corrosion behavior of X80 pipeline steel have been investigated in coastal saline soil using polarization curves, electrochemical impedance spectroscopy, weight-loss test and surface analysis techniques. Results show that the corrosion rate of the steel specimen decreases with the AC frequency increasing, when the AC frequency is 20 Hz, the corrosion rate is about 5.9 times higher than that without the AC interference, and the corrosion rate is only 1.5 times higher than that without the AC interference when the AC frequency increasing to 400 Hz. There is a power function relationship, y = 1.66x −0.5, between the corrosion rate and the AC frequency. At low AC frequencies, the corrosion product films formed on the specimen surfaces contain more defects (holes and tunnels) than those at high frequencies, resulting in severe pitting corrosion.